Development of an ELISA to detect circulating anti‐asparaginase antibodies in dogs with lymphoid neoplasia treated with Escherichia colil‐asparaginase3. (18th December 2012) - Kidd, J. A.; Ross, P.; Buntzman, A. S.; Hess, P. R.
Abstract Resistance to Escherichia colil‐asparaginase in canine lymphoma occurs frequently with repeated administration, a phenomenon often attributed, without substantiation, to the induction of neutralizing antibodies. To test the hypothesis that treated dogs develop antibodies against the drug, we created an enzyme‐linked immunosorbent assay (ELISA) to measure plasma anti‐asparaginase immunoglobulin G responses. Using samples from dogs that had received multiple doses, specific reactivity against l‐asparaginase was demonstrated, while naïve patients' samples were negative. The optimized ELISA appeared sensitive, with endpoint titers >1 600 000 in positive control dogs. Intra‐ and inter‐assay coefficients of variation were 3.6 and 14.5%. The assay was supported by the observation that ELISA‐positive plasma could immunoprecipitate asparaginase activity. When clinical patients were evaluated, 3/10 dogs developed titers after a single injection; with repeated administration, 4/7 dogs were positive. l‐asparaginase antibodies showed reduced binding to the PEGylated drug formulation. The ELISA should prove useful in investigating the potential correlation of antibody responses with resistance.